(untitled) (Meridiano 47 - Journal of Global Studies, 2017)
Resenha de YERGIN, Daniel. The Quest: Energy, Security and the Remaking of the Modern World. New York: The Pinguin Press, 2011. 801 pg. ISBN 978-1-59420-283-4